Changes in the surface morphology of platinum electrodes produced by the application of periodic potential treatments in alkaline solution - Visintin, Arnaldo (1990)
The development of preferentially oriented crystalline surfaces of Pt with rough topographies in alkaline solution, produced by the application of periodic square wave potential treatments, is described. The influence of the different electrical variables is studied systematically and the characteristics of the different growth modes are followed through voltammetry in the H-atom electrosorption potential range and SEM micrographs. These effects are explained in terms of a strong OH− ion-metal surface interaction which favours the formation of hydrous Pt oxide layers. The electroreduction of the latter yields Pt overlayers with distinguishable growth modes and preferred crystalline orientations.